PENINGKATAN AKTIVITAS BELAJAR DAN KETERAMPILAN BERPIKIR TINGKAT TINGGI PESERTA DIDIK MELALUI IMPLEMENTASI MODEL THINK PAIR SHARE DALAM PEMBELAJARAN MATEMATIKA DI MTs NEGERI 3 REMBANG JAWA TENGAH - Dwijayanti, Ni’mah (Kadikma, 2022)
Higher-order thinking skills are the ability of students to analyze, evaluate, and create. Students with good higher-order thinking skills will have the drive to think broadly and deeply about the subject matter and be able to solve contextual problems based on critical and rational arguments. The results of observations of the mathematics learning process at the research site indicate that students tend to be less active in participating in learning, so high-level learning outcomes tend to be unsatisfactory. To solve these problems, the researchers made improvements to the quality of education by implementing the think pair share model. The learning improvement process was carried out in two cycles. The progress in learning indicates that students' learning activities and higher-order thinking skills have increased. Students' learning activities have grown from the initial cycle to the final stage of the learning process. The improvement in learning also shows that students' higher-order thinking skills have increased after taking action. Higher-order thinking skills of students have improved from the initial cycle to the final stage, with the average value in the initial cycle, cycle 1, and cycle 2, respectively, being 35, 55, 95. The average higher-order thinking skill has increased from the initial stage to the final stage, from the initial condition to cycle 1 of 57.14%, and cycle 1 to cycle 2 of 72.73%. The research results obtained are under the indicators of research success, namely improving learning through implementing the think pair share model, successfully increasing learning activities, and students' higher-order thinking skills. Keywords: think pair share, aktivitas, keterampilan berpikir tingkat tinggi